Peran Strategis Kepemimpinan dalam Merancang dan Mengimplementasikan Model Pembaharuan Lembaga Pendidikan - Gita Selvia; Imamul Muttaqin (Reflection : Islamic Education Journal, 2024)
Educational institutions play a vital role in shaping human resources and adapting to rapid changes. To address globalization and technological challenges, they must implement effective and sustainable reforms, with strategic leadership as a key driver. This study examines the role of strategic leadership in designing and implementing renewal models in educational institutions. It identifies factors influencing success and offers recommendations for effective practices. Strategic leadership is crucial in enhancing educational quality and system effectiveness. Leaders act as internal change agents, develop innovative strategies, and coordinate resources to achieve reform goals. Using library research methods, this study reviews literature, including books, journal articles, and research reports on strategic leadership and educational reform. Data analysis involves identifying themes, theories, and best practices. Findings reveal that strategic leaders function as visionaries, motivators, facilitators, and resource managers. Their effectiveness depends on clear strategy formulation, consensus-building, and resistance management. Support from stakeholders, effective communication, and community involvement are pivotal for successful reform implementation. This study emphasizes the importance of strategic leadership in fostering transformative changes within educational institutions.